2004
DOI: 10.1002/yea.1180
|View full text |Cite
|
Sign up to set email alerts
|

Bax‐induced cell death in Candida albicans

Abstract: Bax is a pro-apoptotic member of the Bcl-2 family of proteins involved in the regulation of genetically programmed cell death in mammalian cells. It has been shown that heterologous expression of Bax in several yeast species, such as Saccharomyces cerevisiae, Schizosaccharomyces pombe and Pichia pastoris, also induces cell death. In this study we investigated the effects of Bax expression in the pathogenic yeast Candida albicans. Cell death inducing expression of Bax required a synthetic BAX gene that was codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…These results are similar to results that were previously reported in S. cerevisiae, suggesting a common mechanism in C. gloeosporioides (De Smet, 2004;Ligr et al, 1998;Madeo et al, 2004). We also showed that Bcl-2 expression delayed natural fungal death due to aging and reduced the sensitivity of the fungus to moderate environmental stresses including UV, temperature, and oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are similar to results that were previously reported in S. cerevisiae, suggesting a common mechanism in C. gloeosporioides (De Smet, 2004;Ligr et al, 1998;Madeo et al, 2004). We also showed that Bcl-2 expression delayed natural fungal death due to aging and reduced the sensitivity of the fungus to moderate environmental stresses including UV, temperature, and oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…We also showed that Bcl-2 expression delayed natural fungal death due to aging and reduced the sensitivity of the fungus to moderate environmental stresses including UV, temperature, and oxidative stress. Similar results have been reported in budding yeast and plants where Bcl-2 expression promoted longevity and provided protection from biotic (including pathogenic fungi) and abiotic stresses (Borner, 2003;De Smet et al, 2004;Igaki and Miura, 2004;Madeo et al, 2004). Notably, Chen and Dickman (Chen and Dickman, 2005;Dickman et al, 2001) recently reported that elevated endogenous levels of reactive oxygen species (ROS) lead to apoptotic cell death in a related Colletotrichum species.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Ultrastructural analysis revealed more frequent cell necrosis-like phenotypes in cells of the Ab ΔtmpL conidia compared with seemingly intact wild-type conidia (Figure 5C, TEM). In order to clarify the TEM observation, we determined the percentage of old conidia that stained positive with annexin V-FITC, a compound that specifically stains apoptotic or dead cells by binding to phosphatidylserine present on the outer leaflet [58],[59]. The annexin V-stained conidia from 21-day-old Ab ΔtmpL strain were increased significantly to 30%, whereas the annexin V-positive wild-type conidia had increased less than 10% after 21 days of growth on CM (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Heterologous expression of the human key apoptotic inducer Bax causes rapid cell death in the yeast Saccharomyces cerevisiae [51,52] and Candida albicans [53]. Manon and colleagues demonstrated that Bax expression induces the release of cytochrome c from mitochondria-a hallmark of mammalian Bax action [25].…”
Section: Mitochondrial Cell Death Regulation By Heterologous Expressimentioning
confidence: 99%